Implementasi Matakuliah Qashashul Quran Terhadap Kemampuan Mahasiswa Program Studi PIAUD Dalam Berkisah - Aisyah Amatul Qayyum; Mawaddah Ulya; Malikatus Sholihah (Alzam: Journal of Islamic Early Childhood Education, 2024)
His study is a qualitative research aimed at describing the ability of students of the Early Childhood Islamic Education Study Program in telling stories in the qashashul qur'an course. Data collection techniques used are interviews, observation and documentation. The data is then analyzed by inductive analysis techniques. Based on the results of the study, it can be seen that as the learning objectives, namely: students are brave / confident to appear to tell stories, students tell stories according to good storytelling rules for early childhood, students are able to provide wisdom from the stories conveyed can be achieved. From the research above, it can be concluded that in telling stories, things that need to be considered are as often as possible to practice or perform, this can increase students' courage, train themselves to get used to speaking, have a lot of story references, and can provide wisdom or moral messages to be conveyed.